Isolasi dan Identifikasi Aktivitas Bakteri pada Air Batang Bungo - Indri Artanti; Ardi Mustakim (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Batang Bungo River faces severe pollution from domestic waste and illegal gold mining, which has led to an increase in skin diseases and diarrhea among residents of Tanjung Gedang, exacerbated by poor physical-chemical water quality, including low pH and high levels of Total Suspended Solids (TSS) and Chemical Oxygen Demand (COD), all of which foster the growth of pathogenic microorganisme. This study aimed to identify bacteria and fungi present in Batang Bungo River water, characterizing their colony morphology and microscopic structures to understand the impact of pollution on microbial communities. The methodology involved serial dilution of water samples, followed by inoculation onto Nutrient Agar (NA) media using the pour plate technique, and incubation at 37°C for 24-48 hours. Macroscopic observations of colonies (color, shape, texture) were performed, and representative colonies were stained with crystal violet for microscopic observation at 1000x magnification to identify cellular and hyphal structures. The results indicated the presence of various microorganisms, including Gram-positive bacteria, filamentous fungi, and possibly protozoa, with colonies exhibiting characteristics such as off-white color, rough surfaces, and irregular edges. Microscopic examination after crystal violet staining revealed rod-shaped (bacilli), spherical (cocci) structures, and branched filamentous structures resembling hyphae, consistent with a mixture of bacteria and filamentous fungi. The identification of pathogens like Clostridium, Dermatophilus, and Escherichia coli in previous studies, coupled with the poor water quality, confirms significant microbiological and chemical contamination. Crystal violet proved effective as a stain for microscopic identification of microorganism structures. In conclusion, the water quality of Batang Bungo River is highly concerning and requires serious attention for monitoring and management to safeguard public health and the river ecosystem.